Advancing Firm-Level Digital Technology Diffusion: A Hybrid Bibliometric and Framework-Based Systematic Literature Review - Qingyue Shi; Lei Shen (Systems)
The rapid proliferation of digital technologies across industries has created significant opportunities for enterprises, yet a comprehensive and integrated review of digital technology diffusion (DTD) at the firm level remains underexplored. This study addresses this gap by systematically analyzing 87 research articles published between 1993 and June 2024 in top-tier management and business journals (ranked A* or A in the ABDC-JQL 2022), sourced from the Web of Science database. Employing a hybrid review methodology that combines bibliometric and framework-based reviews, this study provides a comprehensive overview of the existing research on firm-level DTD. By leveraging the established theories, contexts, methods, antecedents, decisions, and outcomes (TCM-ADO) framework, we consolidate fragmented insights and propose future research directions. This study pioneers the application of the TCM-ADO framework to DTD, offering a novel taxonomy that advances theoretical development.